2015
DOI: 10.1007/s12230-015-9457-5
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplex Reverse Transcription (RT) High-Fidelity PCR Protocol for the Detection of Six Viruses that Cause Potato Tuber Necrosis

Abstract: Viruses that cause necrotic symptoms in potato tubers can be difficult to distinguish based on symptoms and frequently require multiple molecular tests to identify the pathogen. In this study, a multiplex RT PCR high fidelity PCR protocol was developed using previously validated primers that could accurately detect six important potato viruses and detect multiple viruses in a single sample simultaneously. To test the protocol, 53 tubers previously tested using conventional PCR were retested using this multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have shown the effectiveness of multiplex PCR in the simultaneous detection of three (Chiquito-Almanza et al, 2017 ), six (Cating et al, 2015 ), seven (Kwon et al, 2014 ; Zhao et al, 2015 ), eight (Kwak et al, 2014 ), and up to nine (Gambino, 2015 ) pathogens. The purpose of our optimization of multiplex PCR was to develop a robust, flexible, and accurate diagnostic tool for the detection of the identified viruses, as they produce similar symptoms and can be found within their hosts in multiple co-infections.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the effectiveness of multiplex PCR in the simultaneous detection of three (Chiquito-Almanza et al, 2017 ), six (Cating et al, 2015 ), seven (Kwon et al, 2014 ; Zhao et al, 2015 ), eight (Kwak et al, 2014 ), and up to nine (Gambino, 2015 ) pathogens. The purpose of our optimization of multiplex PCR was to develop a robust, flexible, and accurate diagnostic tool for the detection of the identified viruses, as they produce similar symptoms and can be found within their hosts in multiple co-infections.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other techniques of PLRV detection, the proposed silver-enhanced LFIA is more sensitive than previously-described LFIAs in conventional format with an LOD of 30 ng/mL (Kondakova, Butenko, Skurat, & Drygin, 2016) and more rapid than tissue print immunoassay with a duration of 4-5 h (Samsatly, Jawhari, Najjar, Sobh, & Abou-Jawdah, 2014). Moreover, due to possibility of on-site application, this LFIA is a good alternative for PLRV assays based on reverse transcription polymerase chain reactions (Cating, Funke, Kaur, Hamm, & Frost, 2015;Ju, 2011;Zhang et al, 2017) or loop-mediated isothermal amplification (Ahmadi, Almasi, Fatehi, Struik, & Moradi, 2013;Almasi, Manesh, Jafary, & Dehabadi, 2013).…”
Section: Comparison Of Lfias Without Enhancement and With Silver Enhamentioning
confidence: 97%
“…Multiplex PCR assays were preferred by numerous plant virologists to define simultaneously multiple virus infections in cultivated crops (Nie and Singh, 2000;Saade et al, 2000). Concurrent amplification of plant-pathogen viruses, viroids, and phytoplasma by multiplex PCR assays was reported in sweet potato and potato (Kwak et al, 2014;Cating et al, 2015), in stone fruits (Sánchez-Navarro et al, 2005) in wheat (Tao et al, 2012;Hassan et al, 2018), in tobacco (Günay and Usta, 2020), in grapevine (Gambino and Gribaudo, 2006), in cucurbits (Kwon et al, 2014), in chrysanthemum (Zhao et al, 2015), in barley and triticale (Trzmiel, 2017), in the citrus tree (Roy et al, 2005), and in garlic (Park et al, 2005).…”
Section: Infection Incidences Of Bydvs Using By Multiplex Rt-pcr and ...mentioning
confidence: 99%